(untitled) (Physical Education, Health and Social Sciences, 2025)
In August 2021, after the withdrawal of American and NATO forces from Afghanistan; a vacuum for investments and reconstruction was created. As immediate neighbor of Afghanistan: China having historical links with Afghanistan, there began a new era of cooperation between them. This cooperation is multifaceted which led to the development of Afghanistan. However, it also brought some long and short-term implications for Pakistan. This research study examines and explains that how the Sino-Afghan cooperation became strong especially after controlling of Afghan state of affairs by Emarat e Islami Afghanistan popularly known as Taliban in 2021 and how this cooperation will have implications for Pakistan. The study finds that Pakistan will be having opportunities of cooperation with both the nations in the current scenario, but the challenges faced in this backdrop will also be enormous due to the game spoilers and proxies there. In recommendations the study suggests some measures that what strategy Pakistan needs to mitigate the potential risks and avail the opportunities in the future.